Pitt Street pirates - Deary, Terry; Donald, Steve (Minneapolis : Stone Arch Books, 2006)
While trying to beat their town's "golf club kids" in a treasure hunt, Captain Roger Redbeard, Sniffles the Cabin Boy, and Ellie, a band of modern-day pirates, uncover a real treasure.
3.4
5-8
Keywords: Pirates -- Juvenile fiction; Treasure troves -- Juvenile fiction; Buried treasure -- Fiction; Humorous stories; Pirates -- Fiction; Buried treasure -- Fiction; Humorous fiction; Pirates -- Fiction